Zur Konsistenz von Abweichungsanalysen in hierarchischen Kennzahlensystemen - Rudolf Vetschera (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1993)
Hierarchische Kennzahlensysteme stellen eine bedeutende konzeptuelle Grundlage für Management- Informationssysteme dar. In dieser Arbeit wird ein bisher unberücksichtigter Aspekt der Abweichungsanalyse in derartigen Kennzahlensystemen aufgegriffen: die Konsistenz der als signifikant ausgewiesenen Abweichungen über mehrere Hierarchiestufen des Kennzahlensystems hinweg. Es wird gezeigt, daß Zusammenhänge zwischen den auf unterschiedlichen Hierarchiestufen ausgewiesenen Abweichungen nur unter recht einschränkenden Voraussetzungen hergestellt werden können und die Bedeutung derartiger (In-) Konsistenzen für die Abweichungsanalyse wird diskutiert. – – Hierarchical indicator Systems are an important theoretical basis for the development of management information Systems. Such indicators are mainly used to determine deviations between planned and actual values of indicators. In this paper, we analyze the consistency of such deviations across hierarchical levels. We show that a systematic relationship between deviations at lower and higher levels of the indicator System can be established only under rather restrictive conditions. This observation holds both for a very simple model, in which deviations are considered significant if they exceed a certain threshold in one direction only and upper level indicators are derived from lower level indicators by basic operations, as well as for more complex situations, in which deviations are described e.g. by membership functions of fuzzy sets. The implications of these results for the analysis and use of hierarchical indicator Systems are also discussed.
Keywords: 330